HOW IS HOT-SEAT GAME IN THE EFL STUDENTS’ PERCEPTION IN LEARNING ENGLISH SPEAKING SKILL? - Syahroni, Ali Imron; Wahono, Suparwoto Sapto (Universitas PGRI Sumatera Barat, 2024)
English is a subject that not all students like. Teachers need media to make students enjoy learning English. One of media is Hot Seat game. Hot seat game is a game that is played in groups with the aim of honing their speaking skills and their vocabulary. In playing Hot Seat game they will naturally add their vocabularies in English, which helps in speaking skills. There were two research objectives on this research, namely: 1) to describe the students’ perception of hot seat game to stimulate them in learning English. 2) To describe the students' understanding of the use of the hot seat game in learning speaking skills. This research used descriptive research by qualitative approach. The subjects were 20 students from class XI SMA Istiqlal. The data was collected by observation, and interview. The data were analyzed by using technique which consisted of data collection, data condensation, data display and conclusion drawing. To check the validity of data, writer used source and method triangulation. There were two findings in this study namely 1) Students felt happy when the class implemented hot seat games. 2) Students were satisfied that by using hot seat they added new vocabulary for English Speaking skill. In speaking skills, the students have to be able to choose the right word, pronunciation, intonation, and sentence construction.